(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The early 1990s saw a new phenomenon emerge in Ghana – it was the beginning of private higher education following the deregulation of the higher education sector. Since then, there has been an upsurge in growth and currently, there are 118 private universities dotted around the country. Although the emergence has increased access to higher education, it has presented concerns about the compromise of quality and standards in the sector. The aim of the study was to evaluate the internal quality assurance processes at selected private universities in Ghana with the view to developing a quality assurance model for the higher education sector. Using mixed qualitative research methodologies, the key findings were that the existing internal quality assurance practices focused mainly on planning and implementing the plan. The study concluded that there was a need for private universities to strengthen monitoring and evaluation, data collection, acting on feedback and benchmarking tools.